2012
DOI: 10.1124/dmd.112.048736
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of a Novel Cyp2a(4/5)bgs-Null Mouse Model

Abstract: Knockout mouse models targeting various cytochrome P450 (P450 or CYP) genes are valuable for determining P450's biologic functions, including roles in drug metabolism and chemical toxicity. In this study, a novel Cyp2a(4/5)bgs-null mouse model was generated, in which a 1.2-megabase pair genomic fragment containing nine Cyp genes in mouse chromosome 7 (including, sequentially, Cyp2a5, 2g1, 2b19, 2b23, 2a4, 2b9, 2b13, 2b10, and 2s1) are deleted, through Cre-mediated recombination in vivo. The resultant mouse st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…1A). As reported recently, the anti-CYP2A5 polyclonal antibody detects a nonspecific band in the lungs of both Cyp2a5-null mice and the CYP2A13-humanized mice (Wei et al, 2013). As expected, the CYP2A13 band was not detected in lung microsomes from the Cyp2a5-null mice, which served as a negative control.…”
Section: Resultssupporting
confidence: 83%
“…1A). As reported recently, the anti-CYP2A5 polyclonal antibody detects a nonspecific band in the lungs of both Cyp2a5-null mice and the CYP2A13-humanized mice (Wei et al, 2013). As expected, the CYP2A13 band was not detected in lung microsomes from the Cyp2a5-null mice, which served as a negative control.…”
Section: Resultssupporting
confidence: 83%
“…Here, we used a Cyp2a(4/5)bgs-null mouse model (Wei et al, 2013) to study the impact of nicotine metabolism on nicotine's pharmacological and behavioral effects. In this mouse model, a number of P450 genes known or potentially involved in nicotine metabolism are deleted, including two Cyp2a (2a4 and 2a5) and all five Cyp2b (2b9, 2b10, 2b13, 2b19, and 2b23).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown possible roles of b-catenin and the two-pore K + channel Kcnk1 in the sex difference in PB-induced the hepatocyte proliferation (Braeuning et al, 2011;Saito et al, 2013). PB is not a preferred substrate for CYP2B (Pacifici, 2016), although the clearance of another barbiturate, pentobarbital, in mice appeared to involve enzymes encoded by the Cyp2a(4/5)bgs gene cluster (Wei et al, 2013). It is unclear whether the loss of the Cyp2abgs genes would cause a change in PB metabolism, but there has been no report demonstrating a role for PB metabolites in stimulating hepatocyte proliferation.…”
Section: Cyp2b and Pb-induced Hepatocyte Proliferationmentioning
confidence: 96%
“…Among the deleted genes, only Cyp2a4/5 and Cyp2b9/10/13 are expressed in liver, and Cyp2a4 and Cyp2b9/13 are female predominant (Damiri et al, 2012;Li et al, 2013). The deletion of the gene cluster did not lead to any notable developmental or morphologic changes, and there was no significant compensatory change in the expression of CPR or various other major P450 enzymes, including CYP2C, CYP3A, CYP2E1, and CYP1A1/2 (Wei et al, 2013). A report of a Cyp2b-knockdown mouse also showed absence of any notable biologic phenotypes (Damiri et al, 2012).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation